Complex systems approach to the study of posture and locomotion in older people - Moraes, Renato; Mauerberg-deCastro, Eliane [UNESP] (Springer Nature, 2017)
Traditionally, the aging process has been viewed as something negative, a phenomenon that eventually results in frailty. However, the development and adaptive processes involved with the aging process are now understood as part of a nonlinear, systemic reorganization of the body. This view sees the aging body-a biological system-as having subsystems that interact at different levels and with different time scales. In the present chapter, we discussed some concepts associated with the aging process. We began by using a dynamic systems perspective to discuss changes in movement patterns of older individuals. According to this perspective, effects of the aging process are not due to isolated changes in different structures, but to collective changes in interacting subsystems. We then presented the role of functional variability, in particular addressing postural control by illustrating that increases in body sway can be the result of an active exploration of the limits of stability. In the last two sections, we discussed in more detail how the application of the dynamic systems approach can help to explain older adults' postural control strategies, as well as the flexibility of their gait patterns. We employed general concepts of a dynamic systems perspective to discuss the aging process, using the notions of variability, adaptive potential, and complex multi-scale levels or dimensions and multi-time sources of constraints. Specifically, we included the functional role of aging on posture and locomotion control.
Keywords: Aging; Dynamic systems; Haptic information; Locomotion; Posture; Variability